2015
DOI: 10.1088/0004-637x/801/2/92
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Fading and Expansion in the “Miniature Supernova Remnant” of Gk Persei

Abstract: We report on a second epoch of Chandra X-ray imaging spectroscopy of the spatially-resolved old nova remnant GK Persei. An ACIS-S3 observation of 97.4 ks was conducted in November 2013 after a lapse of 13.8 years from the last visit in 2000. The X-ray emitting nebula appeared more faint and patchy compared with the first epoch. The flux decline was particularly evident in fainter regions and the mean decline was 30-40% in the 0.5-1.2 keV energy band. A typical expansion of the brightest part of the remnant was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…The density estimates of the circumbinary material of two different works have been considered (Anupama & Kantharia 2005; Takei et al 2015). The radius of a 'bullet' or knot was taken to vary between 5x10 14 to 1x10 15 cm and the density from 1.5x10 3 cm −3 to 5.5x10 3 cm −3 , following S12 and Verro (2015), see Fig. 14.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The density estimates of the circumbinary material of two different works have been considered (Anupama & Kantharia 2005; Takei et al 2015). The radius of a 'bullet' or knot was taken to vary between 5x10 14 to 1x10 15 cm and the density from 1.5x10 3 cm −3 to 5.5x10 3 cm −3 , following S12 and Verro (2015), see Fig. 14.…”
Section: Discussionmentioning
confidence: 99%
“…The radius of a 'bullet' or knot was taken to vary between 5x10 14 to 1x10 15 cm and the density from 1.5x10 3 cm −3 to 5.5x10 3 cm −3 , following S12 and Verro (2015), see Fig. 14. Density estimates from Takei et al (2015) lead to hydrodynamic timescales of 333 to 1965 years, whereas those of Anupama & Kantharia (2005) vary from 1775 to 8239 years. Using the densities mentioned above, we can estimate the hydrodynamic timescale according to the velocity half-lives of S12 (58 years and 220 years) and of L12 (100 to 6000 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the radio and HST images of RS Oph (Hjellming et al 1986;Taylor et al 1989;O'Brien et al 2006;Bode et al 2007;Rupen et al 2008;Sokoloski et al 2008)-the most studied nova blast wave to dateobservations of other novae have shown similar characteristics. Examples include infrared interferometry of V1663 Aql revealing asymmetry (Lane et al 2007), both radio and optical HST observations of light echoes revealing an asymmetric remnant of T Pyx outbursts (Sokoloski et al 2013) together with optical spectroscopy suggesting bipolarity in its 2011 outburst (Shore et al 2013;Tofflemire et al 2013), radio observations of V959 Mon Linford et al 2015) revealing bipolar structure, optical, radio, and X-ray imaging observations of asymmetry in the GK Per nova remnant (Bode et al 2004;Takei et al 2015), and UV spectroscopic and IR interferometric evidence of a bipolar ejection in V339 Del (Schaefer et al 2014;Skopal et al 2014).…”
Section: Collimation and Asymmetrymentioning
confidence: 99%
“…The barrel with polar over-densities structure presented here, as well as the basic bullet crushing time calculation support their finding. Takei et al, 2015 indicates the system is moving through less dense material than during the time of the observations of Balman, 2005. The derived morphology is decidedly oblate, in contrast to the shapes of other nova shells e.g.…”
Section: Discussion and Questionsmentioning
confidence: 99%